Induced Innovation: Evidence from China's Secondary Industry - Belton M. Fleisher; William H. McGuire; Xiaojun Wang; Min Qiang Zhao (Institute of Labor Economics (IZA), 2020)
We investigate the effect of rising labor costs on induced technological change in China's secondary industry. While previous studies have focused primarily on induced technology change in agriculture and in energy production/environmental protection, there has been little evidence relating to China's adjustments as rising labor costs affect its global competitiveness in the manufacturing sector. Building on insights developed in a rich literature, we propose a model linking changes in labor productivity to changes in labor costs, and the availability of physical capital. Importantly, we derive testable hypotheses to distinguish induced innovation from standard substitution of capital for labor under fixed technology. These hypotheses are tested using both firm- and provincial-level data. Our empirical results support the hypothesis that rising wages have induced labor-saving innovation in China, at least in the decade of the 1990s, but less so or not at all after the middle of the next decade.
Keywords: O30; D22; D24; D33; 330; induced innovation; labor productivity growth; China